Interactions in local governments’ spending decisions: evidence from Portugal - Costa, Hélia (2015)
This paper aims to analyse the degree of interaction between Portuguese municipalities’ expenditure levels by estimating a dynamic panel model, based on jurisdictional reaction functions. The analysis is performed for all 278 Portuguese mainland municipalities from 1986 to 2006, using alternative ways to measure neighbourhood. Results indicate that local governments’ spending decisions are significantly and positively influenced by the actions of neighbouring municipalities. Attempts to identify the sources of interaction allow it to be concluded that they are due to spillovers that require coordination in expenditure items and to mimicking behaviour possibly to attract households and firms.